Pengaruh Gaya Kepemimpinan Kepala Sekolah, Motivasi Kerja, dan Kepuasan Kerja Terhadap Kinerja Guru SMA Di Kecamatan Tanjung Priok - Ismail Dwi Cahyo (Jurnal Ilmiah Wahana Pendidikan, 2019)
This study aims to determine and analyze the influence of principals' leadership style, work motivation, and job satisfaction on the performance of high school teachers in Tanjung Priok Subdistrict. Both directly and indirectly. The population in this study were teachers in Tanjung Priok Subdistrict, amounting to 136 (one hundred and thirty six) people. A sample of 100 (one hundred) people. Sampling used the stratified proportionate random sampling method. Data collection using questionnaires, then analyzing data by path analysis using SPSS version 23.0. The results showed a significant positive effect between the principal's leadership style on work motivation (1), the principal's leadership style on job satisfaction (2), the principal's leadership style on teacher performance (3), work motivation on job satisfaction (4), work motivation on teacher performance (5), and job satisfaction on teacher performance (6). The overall effect is 44.08% directly and indirectly, while the rest of 55.92% is a factor influence other factors not examined in this study.